Te-Doped Cu2Se nanoplates with a high average thermoelectric figure of merit. Issue 23 (27th May 2016) - Yang, Lei; Chen, Zhi-Gang; Han, Guang; Hong, Min; Huang, Liqing; Zou, Jin
Abstract : Te-doped Cu2 Se nanostructures with a high average ZT value for Cu2 Se0.98 Te0.02 . Abstract : Understanding the impact of dopants can direct the design of high-performance thermoelectric nanomaterials. In this study, we use Te as a dopant to modify Cu2 Se nanoplates. It has been found that Te can be uniformly doped and distributed in the synthesized products to form Cu2 Se1− x Te x nanoplates with controlled Te content. Also, a phase transition from the original β-phase Cu2 Se nanoplates to α-phase Cu2 Se1− x Te x nanoplates was observed with increasing Te doping level. From the thermoelectric evaluation of the sintered pellets of Cu2 Se1− x Te x nanoplates, it was found that Te can effectively modify their thermoelectric properties, especially their electrical transport properties. Finally, a high average figure-of-merit value of ∼1.2 in the temperature range from 400 K to 850 K was observed for the Cu2 Se0.98 Te0.02 sample.